Water sources of the Lombok, Ombai and Timor outflows of the Indonesian throughflow - Guo, Yaru; Li, Yuanlong; Yang, Dezhou; Li, Yuxuan; Wang, Fan; Gao, Guandong (Frontiers in Marine Science, 2023)
The Lombok Strait (LS), Ombai Strait (OS), and Timor Passage (TP) are three major outlets of the Indonesian Throughflow to the Indian Ocean. Here, sources and pathways of the LS, OS, and TP outflows are explored by a Lagrangian particle tracking analysis based on a ~3 km regional ocean model simulation. The Makassar Strait transport contributes to ~80%, ~75%, and ~45% of the LS, OS, and TP outflows, respectively. However, ~41% and ~19% of the TP and OS outflows stem from the Lifamatola Passage, which largely feeds the upper and intermediate layers of the outflows. The role of Karimata Strait is quite limited and restricted to the upper layer. It takes 1-2 years and 2-6 years for the Makassar Strait water to reach the OS and TP, respectively, whereas the Lifamatola Passage water passes through the OS (2-6 years) and TP (3-9 years) on a prolonged transit time. In the Banda Sea, the western boundary current is the main pathway toward the OS, while the waters to the TP tend to take a basin interior route.